2019
DOI: 10.1108/apjml-03-2019-0178
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumers’ intentions to purchase green products in the social media marketing context

Abstract: Purpose The purpose of this paper is to observe consumers’ attitudes toward and intentions to purchase green products on social media and to explore the relationships among social media marketing, perceived consumer effectiveness (PCE), product knowledge, subjective norms, perceived behavioral control, price consciousness and attitudes toward and intentions to purchase green products. In addition, this research attempts to further understand these relationships in different consumer groups. Design/methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
214
3
30

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 207 publications
(264 citation statements)
references
References 68 publications
17
214
3
30
Order By: Relevance
“…Moreover, young consumers are more frequently exposed to the Internet and pay more attention to green advertising. Online questionnaire surveys allow researchers to use less time and effort to reach young target groups (Sun & Wang, 2020). The offline questionnaire survey has a high response rate and can ask open‐ended questions.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, young consumers are more frequently exposed to the Internet and pay more attention to green advertising. Online questionnaire surveys allow researchers to use less time and effort to reach young target groups (Sun & Wang, 2020). The offline questionnaire survey has a high response rate and can ask open‐ended questions.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the social desirability bias, we assured the respondents that their personal information was strictly confidential (Ru, Wang, & Yan, 2018; Wang et al ., 2020). Meanwhile, we also told them that their responses would only be used for research purpose and the data would be kept private (Ru, Qin, & Wang, 2019; Shi, Wang, & Zhao, 2017; Sun & Wang, 2020).…”
Section: Methods and Datamentioning
confidence: 99%
“…When consumers perceive eco-labels as credible, they would prefer products with an eco-label [ 9 ]. Similarly, consumer green advertising receptivity also positively affects their intention [ 15 ]. Zhou et al (2019) [ 10 ] found that when a carbon label was put on the right side, the intention for green products was higher.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…For millennials, online product reviews and self-image congruence had an interplay effect on green consumption behavior [ 17 ]. Additionally, Sun (2020) [ 15 ] suggested that social media marketing positively affected subjective norms and product knowledge, which, in turn, increased purchase intention for green products. However, green advertising skepticism on social media may reduce this preference [ 16 ].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation